A noninvasive mucinous cystic neoplasm with intermediate-grade dysplasia of the pancreas and extensive squamous metaplasia: a case report with clinicopathological correlation - Li Peifeng; Wang Yingmei; Zhang Qingqing; Liu Yixiong; Lv Yang; Wang Zhe (BMC, 2012)
Abstract Squamous metaplasia presenting in noninvasive mucinous cystic neoplasm (MCN) of the pancreas is extremely rare. We described a case of 39-year-old Chinese female with a 5-year history of a slow growing mass in the left upper abdomen and an 18-month history of surgical incision exudation. The patient underwent cystojejunostomy, laparotomy and distal pancreatectomy consecutively because of the initial diagnosis of "pancreatic cyst". The histological section showed columnar mucin-producing epithelium formed small papillary projections and extensively visible squamous metaplasia. Therefore the diagnosis of "noninvasive MCN with intermediate-grade dysplasia of the pancreas and extensive squamous metaplasia" was made finally. The squamous component of the pancreas may be derived from pluripotent stem cells, and may be in association with cystojejunostomy. Virtual slides The virtual slide(s) for this article can be found here http://www.diagnosticpathology.diagnomx.eu/vs/1322364365718540